A theory based survey of UK and USA HCPs views on the promotion of smoking cessation and interrelated cancer preventative behaviours postpartum - Ward, Emma; Nostikasari, Dian; Kurti, Allison; Payton, Jamie; Kassianos, Angelos P.; Spears, Claire Adams; Mitchell, Fiona; Notley, Caitlin (My University, 2018)
Across the UK and USA, postpartum smoking relapse rates are high for women who quit smoking during pregnancy: up to 75% at 12 months. Simultaneously, rates of exclusive breastfeeding and physical activity are low. These three cancer preventative behaviours have complex interactions, for example, smoking relapse often corresponds with discontinuing breastfeeding, and breastfeeding can be seen as a barrier to physical activity.